HUBUNGAN ANTARA MOTIVASI DENGAN PRESTASI KERJA KARYAWAN FINISHING FOLDING PT. KYUNGSEUNG TRADING INDONESIA JAKARTA UTARA - syamsurizal syamsurizal (POLITEKNIK LP3I JAKARTA, 2017)
ABSTRACT Human resources are incredibly crucial for companies, playing a role as a driven tigger of all company activities. By having qualified human resources, the company can easily integrate both its vision ang goals to the employees so that the company's goals can be achieved. This research was conducted in PT. Kyungseung trading indonesia jakarta by using work motivation as the independent variable and performance as the dependent variable. The purpose of this study is to determine the influence of work motivation, consisting of need for achievement, need for affiliation and need for power on the performance of the employees of Witel Bekasi. This research is descriptive and causal. Data were analyzed by using descriptive analysis, multiple linear regression analysis, simultaneous hypothesis test (F test), the partial hypothesis testing (t-test), and the coefficient of determination. Sampling technique used is Proportionate Stratified Random Sampling. Based on the results of the questionnaire with 52 respondents, the assessment of employees' work motivation and performance are in the category of very high. In the hypothesis testing results, Keywords: Motivation, Performance, Human Resources